Potential therapeutic values of quinoline derivatives based on their antibacterial activity. - FARIDA P. MINOCHEHERHOMJI; KIRTIDA K. VAIDYA (International Journal of Pharma and Bio Sciences, 2016)
Quinoline derivatives possess a wide spectrum of antibacterial activity like antiseptic, analgesic, trypanocidal, germicidal, amoebicidal, antitubercular, anthelmintic and pyroplasmosis. Many quinoline derivatives possess antifungal effects. Realizing the medicinal importance of azo compounds and quinoline derivatives, it was considered worthwhile to incorporate these two moieties The work of synthesizing the mono azo dyes like 2-phenyl-4-hydroxy-6,7 substituted quinoline derivatives was especially undertaken to ascertain that such compounds could augment antibacterial activity. The synthesized compounds were tested for their antibacterial activity using Disc Diffusion Technique against Escherichia coli, Salmonella paratyphi B, Bacillus subtilis, and staphylococcus aureus. Different compounds of the parent substitute exhibited different results.